Perinatal outcomes in Malta between 2008 and 2022: a comparison of three 5 yearly epochs - De Battista, Nadine Anne; Gatt, Miriam; Khashu, Minesh (Frontiers in Public Health, 2025)
BackgroundPerinatal and neonatal mortality rates are quality indicators of antenatal, neonatal and postnatal care. This study describes perinatal outcomes for Malta over the 15 year period 2008–2022 to inform future practice and healthcare provision.MethodologyAggregate anonymous data on perinatal outcomes from 2008 to 2022 were obtained from the National Obstetric Information System (NOIS), Directorate for Health Information and Research (DHIR). Data for each variable was grouped into three 5-year intervals (2008–2012, 2013–2017 and 2018–2022) to investigate trends over time.ResultsTotal births increased over time (p-value 0.008), mainly driven by singleton pregnancies (p-value 0.004), while multiple pregnancies remained stable. Live births increased (p-value 0.008), however, there was no statistically significant difference in stillbirth rate. There were no statistically significant changes in post-term, preterm or low birthweight deliveries (p-value 0.73). The neonatal mortality rate showed a downward trend from 4.92 per 1,000 live births for the years 2008–2012 to 3.92 per 1,000 births for the 2018–2022 epoch, but this could not be statistically confirmed. Data for ART pregnancies was only available as of 2013, analysis of which showed a significant increase in trend over the years with a p-value of <0.05.ConclusionThis study’s findings highlight important public health implications for Malta and the world. The stable rates of preterm and low birth weight, and the decline in stillbirths, suggest improvements in maternal and infant health. However, Malta still lags behind the rest of Europe. This along with the overall increase in the number of births, may be attributed to the growing number of immigrants within the pregnant population, who have specific healthcare needs which need specific attention. These results can help inform public health policies and improve maternity and neonatal services in Malta and regions with similarly increasing immigrant populations.